The motives Malaysians volunteers assign for serving as volunteering for SUKMA games / Rozita Abdul Latif ... [et al.] - Latif, Rozita Abdul; Nawi, Nor Fadzilina; Zid, Azlina; Bakar, Noridah Abu; Rajli, Mohammad Adzly (Universiti Teknologi MARA, 2022)
Volunteering activities are positive experiences that attract volunteers to spend their free time to benefit society while increasing the volunteers' job satisfaction and self-esteem (Chang et al., 2012). However, research on the motives of sport volunteers and the impact of volunteerism on the self-esteem of sport volunteers in Malaysia is scarce, and the present study was aimed at contributing to the filling of this knowledge gap. The purpose of this study is to determine the motives Malaysian volunteers assign for serving as volunteering for SUKMA Games. A total of 376 Malaysian volunteers for the SUKMA Games in Perak in 2018 participated in the study. A Volunteer Functions Inventory (VFI) and Rosenberg's Self-Esteem Scale (RSES) were administered to 376 Malaysian SUKMA Games volunteers. Data were collected, collated, analysed and interpreted to ascertain the main findings of the SUKMA Games volunteers' motives and their influence on their self-esteem levels. This study showed that Malaysian volunteers had several motives for volunteering with the highest motive identified as understanding. There was also a significant positive relationship between motive for volunteering and self-esteem level among SUKMA Games volunteers. Overall, all Malaysians volunteered because they had a high motive for volunteering. Volunteering also improved the self-esteem levels of Malaysian sport volunteers.